2018
DOI: 10.1242/dev.160614
|View full text |Cite
|
Sign up to set email alerts
|

Distinct prophase arrest mechanisms in human male meiosis

Abstract: To prevent chromosomal aberrations being transmitted to the offspring, strict meiotic checkpoints are in place to remove aberrant spermatocytes. However, in about 1% of males these checkpoints cause complete meiotic arrest leading to azoospermia and subsequent infertility. Here, we unravel two clearly distinct meiotic arrest mechanisms that occur during prophase of human male meiosis. Type I arrested spermatocytes display severe asynapsis of the homologous chromosomes, disturbed XY-body formation and increased… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 43 publications
(93 reference statements)
1
23
0
3
Order By: Relevance
“…3 e). A keyword search in PubMed produced a clinical report [ 69 ] that identified ZFY overexpression in spermatocytes as a physiological marker of meiotic arrest leading to azoospermia and infertility. Within applicability limitations of these clinical observations [ 69 ], we predicted two candidate SNP markers (rs1388535808 and rs996955491) of a decrease in male reproductive potential, as readers can see in Table S 3 .…”
Section: Resultsmentioning
confidence: 99%
“…3 e). A keyword search in PubMed produced a clinical report [ 69 ] that identified ZFY overexpression in spermatocytes as a physiological marker of meiotic arrest leading to azoospermia and infertility. Within applicability limitations of these clinical observations [ 69 ], we predicted two candidate SNP markers (rs1388535808 and rs996955491) of a decrease in male reproductive potential, as readers can see in Table S 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Both in mouse (de Rooij and de Boer, 2003;Hamer et al, 2008) and in human (Jan et al, 2018), failure of meiotic DSB repair or chromosome synapsis leads to meiotic prophase arrest and subsequent spermatocyte apoptosis. Meiotic arrest prevents the occurrence of univalent chromosomes at the first meiotic M phase, which otherwise could lead to improper chromosome alignment during the first meiotic division and subsequent formation of aneuploid gametes.…”
Section: Discussionmentioning
confidence: 99%
“…Meiotic spread preparations were prepared as previously described (Jan et al, 2018). Alternatively, all cultured cells, including non-adherent cells, were spread on the slides using a cytospin (CELLSPIN, 521-1990, VWR).…”
Section: Cytologymentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on both animal and human testes have revealed that many cell cycle‐associated genes are involved in dysfunctional spermatogenesis (Jan et al, ; Wolgemuth, Manterola, & Vasileva, ), but the cell cycle activity of germ cells in human infertility remains poorly understood. Spermatogonia are the main cells responsible for the activity of the mitotic cell cycle in pre‐meiotic arrest.…”
Section: Discussionmentioning
confidence: 99%